2004
DOI: 10.1097/01.aog.0000123245.48645.98
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Previa: The Impact of Prenatal Diagnosis on Outcomes

Abstract: Good outcomes with vasa previa depend primarily on prenatal diagnosis and cesarean delivery at 35 weeks of gestation or earlier should rupture of membranes, labor, or significant bleeding occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
383
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(405 citation statements)
references
References 14 publications
10
383
1
9
Order By: Relevance
“…It can lead to rapid fetal exsanguination and death [1][2][3][4][5] and the perinatal mortality of undiagnosed VP has been reported to be as high as 60%. 6 The incidence of VP has been reported to range between in 1 in 1200 to 1 in 5000 pregnancies but the condition may have been under-reported. [1][2][3][4][5] A recent systematic review of 10 cohort studies found that the incidence of VP is 0.6 per 1000 pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can lead to rapid fetal exsanguination and death [1][2][3][4][5] and the perinatal mortality of undiagnosed VP has been reported to be as high as 60%. 6 The incidence of VP has been reported to range between in 1 in 1200 to 1 in 5000 pregnancies but the condition may have been under-reported. [1][2][3][4][5] A recent systematic review of 10 cohort studies found that the incidence of VP is 0.6 per 1000 pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…Both cord anomalies are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 5 low-lying placenta. [1][2][3][4][5][6][7][8] VCI and VP type I are also more common in twin pregnancies and monochorionicity doubles the risk for VCI compared to dichorinicity. 11,12 Maternal smoking has been recently reported as a risk factor for VCI and thus potentially of VP.…”
Section: Resultsmentioning
confidence: 99%
“…and Oyelese, et al 2 . The placental location will alter from the first to third trimesters, due to the formation of the lower uterine segment.…”
Section: Other Gestationsmentioning
confidence: 98%
“…This concept of a low lying placenta at the mid‐trimester scan (without placenta praevia in the third trimester) was introduced by Oyelese in 1998 15 as a risk factor and discussed in more recent articles 2 8 …”
Section: Risk Factors At the Mid‐trimester Scanmentioning
confidence: 99%
See 1 more Smart Citation